"Significado del Cuidado que Brinda la Interna de Enfermería a Niños Hospitalizados desde la Perspectiva del Cuidador. Hospital Belén de Trujillo 2011." - Quiroz Peche, Diana Cecilia (2012)
This research is of descriptive, co relational type of cross section, was realized with parents from the Human settlement Lorenzo Sanchez la Valle in order to determine the relation between psychosocial factors with the familiar functioning in parents The sample was conformed by 52 families those who fulfilled the opinion of inclusion. For the data collection; were applied instruments of evaluation : Socioeconomic opinion poll, scale of self-esteem, scale of measurement of the level of stress and some questions about the familiar functioning. The results were tabulated and processed by SPSS 15 version, and presented by single and double entrance tables with a numerical and percentage frequency as well as in graphs. The information was processed and tabulated statistically by means of Square the Chie test (x2) After analysis of the results reached the following conclusions: 1. 54.4% are male and 45.6% female. 2. The age of onset in which students consume snuff has been a greater percentage (42.1%) from 8 to ll years old and the lowest percentage (18.0%) between 15 and 18. 13. The level of self-esteem of adolescents in the study, mostly high (72.4%), 22.2% medium and only 4.4% low 4. The reason that teens use snuff, is a majority (15.8%) out of curiosity, then by imitation (13.2%), feeling attracted to the opposite sex (12.7%) and to a lesser extent by feel alone (5.3%). 5. The influence of snuff consumption is mostly (47.4%) influenced by others and the lowest percentage (3.55%) is influenced by both parents and the mother only by 2.2%. 6. The level of snuff consumption among adolescents is mostly (35.5%) moderate and minority (14.5%) had a high consumption level, it should be noted that 24.1% did not consume snuff. 7. Biopsychosocial factors: sex, age at onset, self-esteem, motives, influences are highly significant in the level of snuff consumption among adolescents, KEY WORDS: age, sex, self-esteem, consumption of tobacco.